O tribunal do júri: papel, ação e composição: Vitória/ES, 1850-1870 - Betzel, Viviani Dal Piero (2006)
This work comments on the building up of the Jury Tribunal in the Brazilian history during the nineteenth century, dealing specifically with the case of the Espírito Santo Province. Created originally as a branch from the Portuguese legislation and solely in charge of the press offenses, the Jury was later on endorsed by the Constitution of independent Brazil. Focusing on the interval when the Judiciary was yet being developed in the country and there was also the coexistence between liberals and conservatives, it is shown how the Jury Tribunal was modified by the promulgation of both the Criminal Code and the Criminal Proceeding Code, in 1830 and 1832, respectively. In the midst of such reforms, the Jury kept itself working unabated, delivering a substantially great number of acquittals than of guilty verdicts. This practice occasioned a varied array of criticism to the jurors actions, pointing mainly to its inefficacy without, however, coming to the extreme of proposing its suppression. Going through the records of Victória s District Court between 1850 and 1870, it was sought to establish the origin, the action and the role of the jurors in the local society, where the pursuit of public order, as well as in Brazil as a whole, was a common goal. When appraising the composition of the Jury, it was tried to identify the possible relations among the litigants involved in a lawsuit, guessing that these bonds might have had an influence on the sentences pronounced. With some answers in hand, it was examined, next, the Jury s overall performance, inquiring about the frequency of its reunions, the kind of felonies under its scrutiny and the verdicts delivered to the defendants. The empirical base drawn upon in this work were the criminal lawsuits submitted to the espírito-santense jurors in Victoria s District during the 1850 to 1870 period, besides the correspondence and communications among authorities such as the Provincial President, the Ministry of Judicial Affairs, the Judges, the Police Chief and others.